A Moderated Mediation Model for Board Diversity and Corporate Performance in ASEAN Countries - E-Vahdati, Sahar; Zulkifli, Norhayah; Zakaria, Zarina (MDPI, 2018)
Despite the major investigations in prior studies for direct links among board diversity and corporate performance, the literature has not covered many indirect associations among them. This article analyzes the association between board diversity (gender and foreigner) and corporate performance by focusing on the mediating role of corporate social responsibility reporting (CSRR) and the moderated mediation role of South East Asian (ASEAN) countries through new institutional theory, which consists of legitimacy and institutional theories. According to a sample of 264 corporates from all industries by using GRI G3 guideline from 2011 to 2013, we found that foreign and gender diversity have partial and full mediation effects in ASEAN countries. The main conclusion of the current article indicates that board diversity affects directly with corporate performance and indirectly with CSRR through moderated path analysis. The implications are valuable for academics, managers, and policy makers who are interested to determine the impact of intervening variables on the board diversity and corporate performance relationship in ASEAN countries.